INTERNALISASI PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI KELAS X SMK NEGERI 2 KINTAMANI: Internalisasi, Pendidikan Agama Hindu dan Budi Pekerti, Karakter Religius - Ni Kadek Suartini, Suartini; Lestawi, I Nengah; Tanu, I Ketut (UHN IGB Sugriwa Denpasar, 2025)
Hindu religious education and ethics as an effort to prepare students to know, understand, live, have piety and have noble character in practicing the teachings of Hinduism. In forming the religious character of students at SMK Negeri 2 Kintamani, they internalize Hindu religious education and ethics. The results of this study indicate: (1) The internalization of Hindu religious education and ethics in shaping the religious character of students in class X SMK Negeri 2 Kintamani is carried out because of the existence of the environment and the influence of modernization on student behavior, learning and religious habits (2) The teacher's strategy in the process of internalization Hindu religious education and ethics in Shaping the religious character of students in class X SMK Negeri 2 Kintamani, includes: learning, habituation and development of school culture. (3) The implications of the internalization of Hindu religious education and ethics in shaping the religious character of students in class X SMK Negeri 2 Kintamani, namely: the cognitive domain (students remember, understand and apply the concepts of Hinduism), the affective domain (students accept and familiarize themselves with the concepts of religious teachings Hinduism), the psychomotor domain (students imitate or follow the concepts of Hinduism). Keywords: Internalization, Hindu Religious Education and Character, Religious Character